JoJo's bizarre adventure. Part 4, Diamond is unbreakable. 7 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2020)
"A multigenerational tale of the heroic Joestar family and their never-ending battle against evil!... Who is this person who claims to be an alien? Did Rohan really witness a grisly murder in a tunnel on the highway? Has Yoshikage Kira finally met his match after all these years--and is it a cat or a plant? Morioh is as chaotic as ever!"--Provided by publisher.